The First World War on the Periphery: The Effect of the Environment on British Soldiers in German East Africa, 1914-1918 - Reagin, Shawn M (Scientia Militaria - South African Journal of Military Studies, 2019)
The First World War in German East Africa was significantly different than the war in Europe. More so than just the geographical difference and that Europe still stands at the forefront of popular memory, the environment of equatorial Africa played an equally significant role as an enemy to the British Army as did the German Army. Rather than just a collection of assorted stories, it is the aim of this article to examine the interaction between the British Army and the environment of German East Africa from 1914-1918 and demonstrate that three environmental factors – climate, disease, and terrain – significantly affected the war and the soldiers that fought in it in a variety of ways, both in terms of military operations and on the human level.